The Correlation of Knowledge Level, Hanging Clothes Habit, and The Existence of Mosquito Larva with The Incidence of DHF in Kupang City - Henderfina Vitasari Umpenawany; Mustakim Sahdan; Afrona E. L. Takaeb (Lontar : Journal of Community Health, 2020)
Dengue fever is an acute fever disease caused by the dengue virus, and it is one of the health problems in the world because it often raises extraordinary events (KLB) with a high mortality rate. Indonesia is one of the countries with a high enough DBD case and often occurs KLB. Many efforts and preventive programs have been done, but the cases of DBD continue to increase annually. This research aims to explain the correlation of knowledge, customs hanging clothes, and water container with the incidence of DBD in the work area Oesapa Puskesmas Kupang City. This is a quantitative research using the cross-sectional study. The population in this study was 72 people with sampling techniques using the total sampling method. Data analysis used is by univariate analysis and bivariate analysis using the chi-Square test. The results of this research show that the factor that has a relationship with the incidence of DBD is knowledge (ρ = 0.000), the habit of hanging clothes (ρ = 0.000), and the presence of mosquito larva (ρ = 0.001). Communities with low knowledge, poor habits in hanging clothes, and low environmental sanitation can increase the occurrence of environmental DBD cases. The need to increase knowledge in society so that people know, to want, and able to independently prevent the occurrence of DBD in the environment.